A grouting repair material for roadbed mud and its preparation method

By modifying the composite materials of epoxy resin, iron sand mixture and coated cured particles, the problem of low efficiency of grouting materials in the sludge treatment of sludge on the roadbed is solved, and rapid curing and hardening in high temperature and humid environments are achieved, and the treatment efficiency and long-term effectiveness are improved.

CN119119686BActive Publication Date: 2025-03-11CHINA RAILWAY CHENGDU RAIL TRANSIT HEALTH MANAGEMENT TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411613196.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-11
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

In the existing track bed sludge treatment, multiple polymer slurries are required to process step by step, resulting in low treatment efficiency. Especially when the maintenance time of subway tracks is short, the efficiency of grouting materials is difficult to meet the needs.

Method used

The composite material of modified epoxy resin, iron sand mixture and envelope cured particles is adopted. Through the preparation method and process of modified epoxy resin, the performance stability and bond strength of the material are improved, and the composite slurry is rapidly cured and hardened in humid environments.

Benefits of technology

The stability and rapid repair effect of grouting materials in high temperature and humid environments are achieved, the construction operation time is shortened, and the efficiency and long-term effectiveness of the sludge-filling and mud-burning treatment of the roadbed are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of infrastructure resin, discloses a grouting repair material for roadbed mud swell and its preparation method, the epoxy resin composite material includes modified epoxy resin, iron sand mixture and coated solidified particles; wherein, the preparation method of modified epoxy resin is as follows: take epoxy resin, add silicon carbide fiber and organic solvent, pressurize and stir, then heat ultrasonic dispersion, cool, and obtain modified epoxy resin; the coated solidified particles include a curing agent and a water-soluble film coated on the surface of the curing agent, and the curing agent includes an amino curing agent and 2,4,6-tris (dimethylaminomethyl) phenol. Using epoxy resin as a base material, it is improved in performance to improve the performance stability of the material itself; combined with the treatment process in the modification process, the bonding strength of the modified material and the resin base material is improved, so as to realize the rapid repair and long-term use of epoxy resin composite materials in the repair and management of railway roadbeds such as subway tunnels.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of infrastructure resins, and in particular to a grouting repair material for roadbed mud bubbling and a preparation method thereof. Background Art

[0002] In traffic environments such as railways and tunnels, the roadbed is prone to mud and slurry due to humid environment, rainwater soaking and other reasons. Roadbed mud and slurry refers to the roadbed of the railway line, that is, the roadbed subgrade under the track, which forms mud due to excessive water soaking or dilution of clay soil. Under the action of the running of vehicles, the mud enters the gaps in the ballast and slurries upward, which will cause problems such as dirty roadbed, poor drainage, and reduced elasticity, reducing the bearing capacity of the roadbed and road surface, thereby affecting the safe, stable and high-speed normal operation of vehicles.

[0003] At present, the problem of mud and slurry on the roadbed is mainly solved by grouting, that is, injecting grouting materials into the gap to fill the gap space, so that the force of the track structure in the gap area is redistributed to avoid stress concentration. The performance of different grouting materials and the mechanical properties of their solids are different, which will lead to significant differences in construction and repair effects. Therefore, according to the characteristics of the use environment and needs, the use of more suitable grouting materials is the key to achieving good repair effects.

[0004] For example, the patent with publication number CN111485922A provides a method for treating water leakage, block falling and mud overflow in ELF railway tunnels. High-permeability epoxy waterproof materials, epoxy sealing putty, acrylate grouting materials and the like are used for primer, plugging and filling to treat water leakage from irregular cracks, expansion joints, settlement joints and other fine cracks in concrete structures, thereby reducing mud overflow and other phenomena. Summary of the invention

[0005] The technical problems to be solved by the present invention are:

[0006] In the existing roadbed mud treatment, multiple polymer slurries are needed for coating, filling, plugging and other treatments. This is because polymer slurries with different characteristics have different focuses or outstanding performance advantages, and are suitable for different use scenarios or steps. For example, high-permeability epoxy waterproof materials have outstanding waterproof film-forming properties, so they are brushed on the contact surface of the two phases. However, it takes a long time to treat multiple slurries in steps, which greatly affects the efficiency of treatment.

[0007] For the subway tracks that have been put into operation, the time available for inspection and maintenance is short due to the long daily working hours of the subway. According to the provisions of JT / T 1185-2018 "Urban Rail Transit Operation Organization Rules", the time for equipment and facility inspection and construction, inventory of materials, and cleaning during non-operating hours of the subway operating lines is about 4 hours a day. That is, when treating the slurry and mud on the roadbed of the subway track, the grouting materials need to have higher efficiency in the processes of processing, molding, and effectiveness, which puts higher demands on the various properties of the grouting materials.

[0008] The technical solution adopted by the present invention is:

[0009] The present invention provides a grouting repair material for roadbed mud bubbling, comprising modified epoxy resin, iron sand mixture and coated solidified particles;

[0010] Wherein, the preparation method of modified epoxy resin is as follows:

[0011] Take epoxy resin, add silicon carbide fiber and organic solvent, stir under pressure, heat and disperse by ultrasonic, and cool to obtain the modified epoxy resin;

[0012] The coated solidified particles include a curing agent and a water-soluble film coated on the surface of the curing agent, and the curing agent includes an amine curing agent and 2, 4, 6-tris(dimethylaminomethyl)phenol.

[0013] Preferably, during the preparation of the modified epoxy resin, the pressurized pressure is 2-10 MPa and the stirring speed is 200-550 rpm.

[0014] Preferably, in the process of preparing the modified epoxy resin, the heating temperature is 40-80° C. and the ultrasonic power is 620-1000W.

[0015] Preferably, the preparation method of the coated solidified particles is as follows: take an amino curing agent and 2, 4, 6-tris(dimethylaminomethyl)phenol respectively in a mass ratio of 1-1.65:1-1.05, mix them, spray a water-soluble film slurry, and form a water-soluble film shell layer after drying to obtain the coated solidified particles.

[0016] Preferably, the water-soluble film slurry accounts for 35-45 wt % of the total mass of the amino curing agent and 2, 4, 6-tris(dimethylaminomethyl)phenol.

[0017] Preferably, the iron sand mixture comprises iron sand, orthoclase, quartz sand and polypropylene fiber.

[0018] The present invention also provides a method for preparing the grouting repair material for the roadbed mud bubbling, comprising the following steps:

[0019] S1 prepares raw materials for standby use;

[0020] S2: Mix the modified epoxy resin, iron sand mixture and polyacrylate, heat and stir; after cooling, add the coated solidified particles, tumble and stir to form a mixed slurry, and obtain the epoxy resin composite material.

[0021] Preferably, in step S2, the heating temperature is 60-80°C, the stirring speed is 150-200 rpm, and the stirring time is 0.5-2h; and the mixture is cooled to 5-20°C.

[0022] Preferably, by mass fraction, the modified epoxy resin accounts for 38-52%, the iron sand mixture accounts for 20-23%, the polyacrylate accounts for 18-22%, and the coated cured particles account for 8-18%.

[0023] The beneficial effects of the present invention are as follows:

[0024] The present invention adopts bisphenol epoxy resin commonly used in the treatment of roadbed mud and slurry as a base material, and improves its performance to enhance the performance stability of the material itself; further, combined with the treatment process in the modification process, the bonding strength between the modified material and the resin base material is enhanced, thereby achieving rapid repair and long-term use of epoxy resin composite materials in the repair and treatment of railway roadbeds such as subway tunnels.

[0025] Modified epoxy resin, coated curing particles and iron sand are mixed and compounded. On the one hand, it promotes the curing and expansion of the composite slurry after absorbing water, and hardens and forms more quickly to meet the operation needs of the subway; on the other hand, after the composite slurry absorbs a large amount of water, it can prevent the water in the gaps of the roadbed from continuing to penetrate into the underground and causing problems such as loosening and collapse of the roadbed.

[0026] Existing grouting materials will cause local high temperature during high-speed train running, which will easily cause the grouting materials to dehydrate and increase brittleness, affecting the normal use of the grouting materials after filling, and causing problems such as mud and mud on the roadbed to occur repeatedly. In the present invention, the epoxy resin is modified to maintain a stable form at high temperatures, thereby maintaining the stability and firmness of the roadbed in the tunnel for a long time, and effectively alleviating the problem of repeated mud and mud on the roadbed of the railway. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0028] The present invention provides a grouting repair material for roadbed mud bubbling, comprising the following components:

[0029] (1) Modified epoxy resin: Silicon carbide fibers are introduced into epoxy resin and treated with high-pressure stirring and high-temperature dispersion to make them fully homogenized and mixed. During this process, a large number of fine microfibers are split on the surface of the silicon carbide fibers to form a fibrillated morphology, which significantly enhances the interfacial bonding between the silicon carbide fibers and the epoxy resin. This not only improves the uniform dispersion of silicon carbide fibers in the resin slurry, but also allows them to maintain a homogeneous state and high mechanical strength under high temperature conditions.

[0030] (2) Iron sand mixture: including iron sand, orthoclase, quartz sand and polypropylene fiber, which are mixed evenly in a mass ratio of 4.5-8:2-5:2-3.5:1.8-3.2 to form a composite iron sand mixture. On the one hand, it serves as a supporting mortar for filling the joints of the concrete roadbed; on the other hand, it releases heat in a water environment. The higher the temperature, the more it can catalyze the curing reaction process of the epoxy resin and the curing agent, thereby shortening the change process from liquid to solid; on the other hand, the mixture contains elements such as iron and aluminum. After hydration, it forms an alkaline environment, maintains the catalytic activity of the curing agent, and provides favorable reaction conditions for the epoxy resin and the amine-based curing agent.

[0031] (3) Coated curing particles: The curing agent is finely dispersed into uniform tiny particles, and a water-soluble film is coated on the surface. That is, in a dry environment at room temperature, the curing agent can be kept stable. During use, due to the humid environment of mud and slurry, the surface water-soluble film dissolves in water, exposing the curing agent and acting on the base material, thereby triggering the curing process of the epoxy resin. That is, according to the characteristics of the use environment, the curing agent maintains a slow-release effect, reducing the workload of on-site preparation in construction environments such as subway tunnels.

[0032] Among them, the curing agent adopts an amine curing agent, such as modified underwater alicyclic amine, modified underwater phenolic amine, polyether amine, etc., and the curing agent also includes 2, 4, 6-tris (dimethylaminomethyl) phenol. The amine curing agent contains extremely active hydrogen, which can achieve electrophilic bonding with the epoxy group in the epoxy resin to form a stable cross-linked structure; further, 2, 4, 6-tris (dimethylaminomethyl) phenol can provide negative charge or lone pair electrons, and form a transition state with the amine group and the epoxy group, thereby promoting the curing of the epoxy resin and promoting the reaction to proceed in the forward direction, that is, improving the curing reaction efficiency and shortening the construction operation time.

[0033] The present invention also provides a method for preparing the grouting repair material for the roadbed mud bubbling, comprising the following steps:

[0034] (1) Prepare raw materials and set aside:

[0035] 1.1 Preparation of modified epoxy resin

[0036] Take epoxy resin, add silicon carbide fiber and organic solvent, pressurize to 2-10MPa, stir at 200-550rpm, heat to 40-80℃, and perform ultrasonic dispersion at a power of 620-1000W. During the above high pressure and ultrasonic treatment, the surface of silicon carbide fiber is stretched by rapid ultra-tension to form a large number of membrane split spinning, thereby giving it extremely strong surface bonding ability; after taking out and cooling to room temperature, an anhydrous modified epoxy resin slurry is obtained.

[0037] 1.2 Preparation of iron sand mixture:

[0038] Iron sand, orthoclase, quartz sand and polypropylene fiber are taken according to the amount, and mixed by ball milling to obtain an iron sand mixture.

[0039] 1.3 Preparation of coated solidified particles:

[0040] The amino curing agent and 2, 4, 6-tris(dimethylaminomethyl)phenol are taken at a mass ratio of 1-1.65:1-1.05, respectively, and wet ball milled, and then mixed to obtain a mixed solidified powder; a water-soluble film slurry is coated on the surface of the mixed solidified powder through a spray granulation process, and the water-soluble film slurry accounts for about 35-45wt% of the total mass of the amino curing agent and 2, 4, 6-tris(dimethylaminomethyl)phenol. After drying, coated solidified particles are obtained.

[0041] (2) Mix the modified epoxy resin, iron sand mixture and polyacrylate, heat to 60-80°C, slowly stir for 0.5-2h, and stir at a speed of 150-200rpm to make them evenly dispersed, and remove the residual moisture, and then cool to 5-20°C; then add the coated solidified particles, tumble and stir to form a mixed slurry, which is the grouting repair material for the ballast bed;

[0042] Wherein, by mass fraction, the modified epoxy resin accounts for 38-52%, the iron sand mixture accounts for 20-23%, the polyacrylate accounts for 18-22%, and the coated solidified particles account for 8-18%.

[0043] In the present invention, targeted solutions are proposed based on the problems faced by the roadbed of the subway tunnel and the actual work progress. Since the curing process of epoxy resin includes a liquid mixing stage, a gel reaction stage, and a solid forming stage, the present invention improves the composition of the grouting material by utilizing the characteristics of the use environment, thereby improving the curing efficiency of the epoxy resin as a whole, shortening the construction operation time, and being more convenient for practical application.

[0044] Example 1

[0045] Take 25 parts by mass of bisphenol A epoxy resin, add 7.5 parts by mass of silicon carbide fiber with a diameter of 1.8±2 μm and 20 parts by mass of isopropanol, first pressurize to 5 MPa, stir at 280 rpm; then restore to normal pressure, heat to 55±5°C, perform ultrasonic dispersion at a power of 850 W for 45 minutes, take out and cool to room temperature to obtain modified epoxy resin slurry, which is set aside;

[0046] 5.5 parts by mass of iron sand, 3.2 parts by mass of potassium feldspar, 2.58 parts by mass of quartz sand and 2.25 parts by mass of polypropylene fiber were respectively measured, wherein the single fiber fineness of the polypropylene fiber was about 1.6 dtex, 0.5 times the volume of anhydrous ethanol was added, ball milled for 20 minutes, mixed and dried to remove the ethanol, and the iron sand mixture was obtained for standby use;

[0047] 3 parts by weight of 2, 4, 6-tris(dimethylaminomethyl)phenol were added to cold water at 3±2°C to precipitate crystals, and then 3.2 parts by weight of modified alicyclic amine curing agent TAC-900 were added and mixed to obtain a cured mixture; a water-soluble film shell layer with a thickness of about 2.5 μm was sprayed on the surface of the mixed cured powder by a spray granulation process, and the mixture was dried to obtain coated cured particles for later use;

[0048] The modified epoxy resin slurry prepared above was mixed with the iron sand mixture, 12.5 parts by mass of polyacrylate was added, and the mixture was placed in a 65°C environment and slowly stirred at 150 rpm for 1 hour. After being taken out, the mixture was cooled to 15±2°C in an ice water bath; the coated and cured particles prepared above were added, and the mixture was tumbled and stirred to obtain an epoxy resin composite material.

[0049] Example 2

[0050] Take 25 parts by mass of bisphenol F epoxy resin, add 7.5 parts by mass of silicon carbide fiber with a diameter of 1.2±2 μm and 20 parts by mass of isopropanol, first pressurize to 5 MPa, stir at 280 rpm; then restore to normal pressure, heat to 55±5°C, perform ultrasonic dispersion at a power of 850 W for 45 minutes, take out and cool to room temperature to obtain modified epoxy resin slurry, which is set aside;

[0051] 5.5 parts by mass of iron sand, 3.2 parts by mass of potassium feldspar, 2.58 parts by mass of quartz sand and 2.25 parts by mass of polypropylene fiber were respectively measured, wherein the single fiber fineness of the polypropylene fiber was about 2.0 dtex, 0.5 times the volume of anhydrous ethanol was added, ball milled for 20 minutes, mixed and dried to remove the ethanol, and the iron sand mixture was obtained for standby use;

[0052] 3 parts by mass of 2, 4, 6-tris(dimethylaminomethyl)phenol are added to cold water at 3±2°C to precipitate crystals, and then 3.2 parts by mass of polyetheramine are added and mixed to obtain a solidified mixture; a water-soluble film shell layer having a thickness of about 2.5 μm is sprayed on the surface of the mixed solidified powder by a spray granulation process, and the mixture is dried to obtain coated solidified particles for later use;

[0053] The modified epoxy resin slurry prepared above was mixed with the iron sand mixture, 12.5 parts by mass of polyacrylate was added, and the mixture was placed in a 65°C environment and slowly stirred at 150 rpm for 1 hour. After being taken out, the mixture was cooled to 15±2°C in an ice water bath; the coated and cured particles prepared above were added, and the mixture was tumbled and stirred to obtain an epoxy resin composite material.

[0054] Example 3

[0055] Take 22 parts by mass of bisphenol A epoxy resin, add 2.5 parts by mass of silicon carbide fiber with a diameter of 1.8±2 μm and 20 parts by mass of isopropanol, first pressurize to 3.5 MPa, stir at 220 rpm; then restore to normal pressure, heat to 55±5°C, perform ultrasonic dispersion at a power of 850 W for 45 minutes, take out and cool to room temperature to obtain modified epoxy resin slurry, which is set aside;

[0056] 5.5 parts by mass of iron sand, 3.2 parts by mass of potassium feldspar, 2.58 parts by mass of quartz sand and 2.25 parts by mass of polypropylene fiber were respectively measured, wherein the single fiber fineness of the polypropylene fiber was about 1.6 dtex, 0.5 times the volume of anhydrous ethanol was added, ball milled for 20 minutes, mixed and dried to remove the ethanol, and the iron sand mixture was obtained for standby use;

[0057] 5 parts by weight of 2, 4, 6-tris(dimethylaminomethyl)phenol were added to cold water at 3±2°C to precipitate crystals, and then 5.8 parts by weight of modified alicyclic amine curing agent TAC-900 were added and mixed to obtain a cured mixture; a water-soluble film shell layer with a thickness of about 2.5 μm was sprayed on the surface of the mixed cured powder by a spray granulation process, and the mixture was dried to obtain coated cured particles for later use;

[0058] The modified epoxy resin slurry prepared above was mixed with the iron sand mixture, 12.5 parts by mass of polyacrylate was added, and the mixture was placed in a 65°C environment and slowly stirred at 150 rpm for 1 hour. After being taken out, the mixture was cooled to 15±2°C in an ice water bath; the coated and cured particles prepared above were added, and the mixture was tumbled and stirred to obtain an epoxy resin composite material.

[0059] Comparative Example 1

[0060] Take 25 parts by mass of bisphenol A epoxy resin, 5.5 parts by mass of iron sand, 3.2 parts by mass of potassium feldspar, 2.58 parts by mass of quartz sand, 2.25 parts by mass of polypropylene fiber, 3.2 parts by mass of modified alicyclic amine curing agent TAC-900 and 3 parts by mass of 2, 4, 6-tris(dimethylaminomethyl)phenol, wherein the single fiber fineness of the polypropylene fiber is about 1.6 dtex, mix, add 12.5 parts by mass of polyacrylate, place in an environment of 65°C, stir slowly at 150 rpm for 1 hour, take out, cool to room temperature, and obtain a grouting material.

[0061] Comparative Example 2

[0062] 6.2 parts by weight of modified alicyclic amine curing agent TAC-900 were added with anhydrous ethanol for wet ball milling, and then the ethanol was evaporated to remove it, and an equal amount of starch was added, and granulation was performed in a fluidized bed; then a water-soluble film shell layer with a thickness of about 2.5 μm was sprayed on the surface of the mixed solidified powder by a spray granulation process, and dried to obtain coated solidified particles for standby use;

[0063] Take 25 parts by mass of bisphenol A epoxy resin, 5.5 parts by mass of iron sand, 3.2 parts by mass of potassium feldspar, 2.58 parts by mass of quartz sand, and 2.25 parts by mass of polypropylene fiber, wherein the single fiber fineness of the polypropylene fiber is about 1.6 dtex, mix them, add 12.5 parts by mass of polyacrylate, place them in a 65°C environment, slowly stir them at 150 rpm for 1 hour, take them out, cool them to room temperature, add the coated and solidified particles prepared as above, tumble and stir them, and obtain a grouting material.

[0064] Comparative Example 3

[0065] Take 25 parts by mass of bisphenol A epoxy resin, add 7.5 parts by mass of silicon carbide fiber with a diameter of 1.8±2 μm and 20 parts by mass of isopropanol, first pressurize to 5 MPa, stir at 280 rpm; then restore to normal pressure, heat to 55±5°C, perform ultrasonic dispersion at a power of 850 W for 45 minutes, take out and cool to room temperature, so as to obtain modified epoxy resin slurry, which is set aside;

[0066] 5.5 parts by mass of iron sand, 3.2 parts by mass of potassium feldspar, 2.58 parts by mass of quartz sand, 2.25 parts by mass of polypropylene fiber, 3.2 parts by mass of modified alicyclic amine curing agent TAC-900 and 3 parts by mass of 2, 4, 6-tris(dimethylaminomethyl)phenol were taken separately, wherein the single fiber fineness of the polypropylene fiber was about 1.6 dtex, and the modified epoxy resin slurry prepared above was added and mixed, and then 12.5 parts by mass of polyacrylate was added, placed in an environment of 65°C, slowly stirred at 150 rpm for 1 hour, taken out, and cooled to room temperature to obtain a grouting material.

[0067] Comparative Example 4

[0068] Take 25 parts by mass of bisphenol A epoxy resin, add 7.5 parts by mass of silicon carbide fiber with a diameter of 1.8±2 μm and 20 parts by mass of isopropanol, first pressurize to 5 MPa, stir at 280 rpm; then restore to normal pressure, heat to 55±5°C, perform ultrasonic dispersion at a power of 850 W for 45 minutes, take out and cool to room temperature to obtain modified epoxy resin slurry, which is set aside;

[0069] 3.2 parts by weight of modified alicyclic amine curing agent TAC-900 and 3 parts by weight of 2, 4, 6-tris(dimethylaminomethyl)phenol were respectively added with anhydrous ethanol for wet ball milling, and the ethanol was evaporated to remove. Then, the mixture was mixed, and an equal amount of starch was added. The mixture was granulated by fluidized bed to obtain solidified particles for later use.

[0070] The modified epoxy resin slurry prepared above was mixed with 5.5 parts by mass of iron sand, 3.2 parts by mass of potassium feldspar, 2.58 parts by mass of quartz sand, and 2.25 parts by mass of polypropylene fiber, and 12.5 parts by mass of polyacrylate were added. The mixture was placed in an environment of 65°C and slowly stirred at 150 rpm for 1 hour. After being taken out, the mixture was cooled to room temperature. The solidified particles prepared above were then added, and the mixture was tumbled and stirred to obtain a grouting material.

[0071] Test example

[0072] Samples: Examples 1-3, Comparative Examples 1-4

[0073] (1) Performance indicators of ballast bed crack grouting repair materials

[0074] According to the general requirements of GB / T50010-2010 "Concrete Structure Design Code" (2015 Edition), combined with the specific provisions of JC / T1041-2007 "Epoxy Resin Grouting Materials for Concrete Cracks" and GB / T50157-2013 "Metro Design Code", the materials used for grouting repair of the roadbed cracks in subway tunnels shall meet the performance indicators shown in Table 1 below:

[0075] Table 1 Performance index of ballast bed crack grouting repair materials

[0076]

[0077] (2) Performance test of epoxy resin composite materials

[0078] 2.1 Viscosity

[0079] As the intermediate layer consolidation body, the fullness of the grouting repair material in the gap space is one of the important factors affecting the repair effect. Since the gap width of the subway shield tunnel ballast is small, the repair material must have good fluidity and permeability to ensure its full diffusion in the gap space. The single cylinder rotation viscometer method specified in GB / T2794-2022 "Determination of viscosity of adhesives" was used to measure the viscosity value of each sample. The results are summarized in Table 2 below:

[0080] Table 2 Viscosity measurement results of different samples

[0081]

[0082] 2.2 Operational time

[0083] The effective grouting amount of the grouting repair material determines the fullness of the filling of the middle layer consolidation body, and the operable time determines the effective grouting amount of the grouting repair material in the gap space. Therefore, measuring and analyzing the operable time of the grouting repair material can better improve the effectiveness of on-site construction and the convenience of actual operation. According to the filling and treatment of mud bubbling in the roadbed in the subway tunnel, the ideal operation time when the grouting repair material is used for filling is 15-60 minutes. According to the provisions of GB / T2794-2022 "Determination of Viscosity of Adhesives", the operable time of each sample slurry is measured, that is, the time from the extrusion of the grouting repair material into the roadbed gap to the viscosity exceeding the specified performance index limit of 200mPa·s, accurate to 5 minutes, and the results are summarized in the following Table 3:

[0084] Table 3 Results of the operable time of different samples

[0085]

[0086] 2.3 Material shrinkage

[0087] Since the grouting repair material is a reaction-curing resin slurry, the material will shrink to a certain extent after curing, causing shrinkage stress at the material bonding interface, resulting in debonding between the material and the ballast bed, creating new gaps, which affects the filling and repair effect. Therefore, the shrinkage of the grouting repair material is also an important consideration. The volume of each sample was measured when it was extruded and the volume after being placed in a simulated ballast bed gap environment (simulated environmental humidity is 90%) and left to stand for 60 minutes. The degree of shrinkage during this process was calculated, and the results are summarized in Table 4:

[0088] Table 4 Material shrinkage test results of different samples

[0089]

[0090] 2.4 Compressive strength

[0091] According to the stress analysis of the track structure and the actual measurement of the dynamic response of the track structure on site, the interface between the ballast and the segment is mainly under pressure in the vertical direction, and the compressive strength of the repair material as the intermediate layer consolidation body is an important guarantee and key factor for the repair effect. Taking Chengdu Metro as an example, the skylight time of Chengdu Metro is generally from 00:30 to 4:30, the on-site construction time is generally from 0:30 to 3:30, and the time of the first train is generally at 5:30, that is, the structure will be subject to the train load 2 hours after construction. Therefore, the grouting repair material is required to reach the design value of the ballast concrete strength within 2 hours after construction. Using the method of GB / T2569-2008 "Test Method for Performance of Resin Castings", each sample is made into a 25cm*25cm*25cm sample block, and the compressive strength of each sample block at different time points after 2h of extrusion is measured. The results are summarized in the following Table 5:

[0092] Table 5 Compressive strength test results of different samples

[0093]

[0094] 2.5 Tensile strength

[0095] In order to ensure the integrity of the grouting repair material and the concrete structure, the tensile strength of the grouting repair material should not be less than the tensile strength design value of the concrete body. According to the provisions of GB / T2568-1995 "Test method for tensile properties of resin castings", each sample is made into a 25cm*25cm*15cm sample block, and the tensile strength of each sample block is measured after curing for 2 hours. The results are accurate to 1MPa. The results are summarized in the following Table 6:

[0096] Table 6 Tensile strength test results of different samples

[0097]

[0098] 2.6 Bond strength

[0099] After the grouting repair material is cured, the bonding strength may decrease. Specifically, it may be manifested as: debonding between the grouting repair material and the concrete interface, damage to the bonding layer of the grouting repair material, damage to the concrete specimen, etc. Therefore, the decrease in bonding strength greatly affects the grouting repair effect. After each sample is squeezed out, it is made into a 25cm*25cm*15cm sample block, which is placed in water at room temperature for curing for 28 days. After taking it out, wipe off the excess water on the surface, and use a tensile testing machine to measure its bonding performance, which is the wet bonding strength; then place it in a room temperature air environment and let it stand for 2 days, and measure its bonding performance, which is the dry bonding strength. The test results are summarized in the following Table 7:

[0100] Table 7 Bond strength test results of different samples

[0101]

[0102] 2.7 Shear strength

[0103] According to the provisions of GB / T7124-2008 "Determination of tensile shear strength of adhesives", the shear strength of each sample after curing for 2 hours was measured, and the results were accurate to 0.1MPa. The results are summarized in Table 8 below:

[0104] Table 8 Shear strength test results of different samples

[0105]

[0106] 2.8 Impermeability pressure

[0107] As an intermediate layer consolidation body that forms an integral part of the ballast concrete, the impermeability pressure of the grouting repair material is an important guarantee and key indicator of the repair effect. The impermeability performance level of the grouting repair material after curing should be consistent with that of the concrete, so as to effectively deal with the problem of mud bubbling on the ballast and control its sufficient impermeability during subsequent use. According to the design requirements for the impermeability level of waterproof concrete in the subway design specification "GB / T50157-2013", the highest level requirement for cast-in-place concrete structures and prefabricated steel frame concrete structures is P12, that is, the maximum impermeability pressure of concrete components is 1.2MPa. According to the provisions of GB18445-2001 "Cement-based penetrating crystalline waterproof materials", a mortar permeameter was used to measure the impermeability pressure of each sample after curing for 2 hours. The results are summarized in the following Table 9:

[0108] Table 9 Test results of anti-seepage pressure of different samples

[0109]

[0110] In summary, according to the use requirements and performance test results of the above-mentioned grouting materials, the grouting repair materials prepared in Examples 1 to 3 can meet the performance indicators required for use in all performance scales, and can achieve good performance after a shorter curing time; while the grouting materials in Comparative Examples 1 to 4 require a longer time to reach the performance standards required for use. This proves that the epoxy resin composite material proposed in the present invention has a more efficient curing process during use, which can shorten the construction time, so that it can be applied to use scenarios such as subway maintenance where grouting repair work needs to be completed in a short time.

[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A grouting repair material for roadbed mud bubbling, characterized in that: The components of the grouting repair material are 38-52% modified epoxy resin, 20-23% iron sand mixture, 18-22% polyacrylate and 8-18% coated solidified particles, wherein the iron sand mixture includes iron sand, orthoclase, quartz sand and polypropylene fiber; Wherein, the preparation method of modified epoxy resin is as follows: Take epoxy resin, add silicon carbide fiber and organic solvent, stir under pressure, heat and disperse by ultrasonic, and cool to obtain the modified epoxy resin; The coated solidified particles include a curing agent and a water-soluble film coated on the surface of the curing agent, and the curing agent includes an amine curing agent and 2, 4, 6-tris(dimethylaminomethyl)phenol.

2. The grouting repair material for roadbed mud bubbling according to claim 1 is characterized in that: In the process of preparing the modified epoxy resin, the pressurized pressure is 2-10 MPa and the stirring speed is 200-550 rpm.

3. The grouting repair material for roadbed mud bubbling according to claim 1, characterized in that: In the process of preparing the modified epoxy resin, the heating temperature is 40-80° C. and the ultrasonic power is 620-1000W.

4. The grouting repair material for roadbed mud bubbling according to claim 1, characterized in that: The preparation method of the coated solidified particles is as follows: The amino curing agent and 2, 4, 6-tris(dimethylaminomethyl)phenol are taken and mixed at a mass ratio of 1-1.65:1-1.05, and then a water-soluble film slurry is sprayed. After drying, a water-soluble film shell layer is formed to obtain the coated solidified particles.

5. The grouting repair material for roadbed mud bubbling according to claim 4, characterized in that: The water-soluble film slurry accounts for 35-45wt% of the total mass of the amino curing agent and 2, 4, 6-tris(dimethylaminomethyl)phenol.

6. The method for preparing the grouting repair material for roadbed mud bubbling according to any one of claims 1 to 5, characterized in that: The steps include: S1 prepares raw materials for standby use; S2: Mix the modified epoxy resin, iron sand mixture and polyacrylate, heat and stir; after cooling, add the coated solidified particles, roll and stir to form a mixed slurry, and obtain the epoxy resin composite material.

7. The method for preparing the grouting repair material for roadbed mud bubbling according to claim 6, characterized in that: In step S2, the heating temperature is 60-80°C, the stirring speed is 150-200 rpm, and the stirring time is 0.5-2h.

8. The method for preparing the grouting repair material for roadbed mud bubbling according to claim 6, characterized in that: In step S2, cooling to 5-20°C.

Citation Information

Patent Citations

  • ELF railway tunnel water leakage, block dropping and grout turning disease treatment method

    CN111485922A

  • Preparation method of resin matrix composite for electrical accessories

    CN108822495A

  • Curable proppant as well as preparation method and application thereof

    CN110079295A